ANALISIS DIMENSI KETEPATAN KEBIJAKAN E-PARKING DALAM MENINGKATKAN PENDAPATAN RETRIBUSI PARKIR DI KOTA SURABAYA - Renata Pradnja Paramitha; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
E-parking policy is an innovative electronic-based parking payment system implemented by the Surabaya City Government for managing on-street parking, aiming to improve parking governance and optimize regional retribution revenue. This policy is based on Surabaya City Regional Regulation Number 3 of 2018 concerning Parking Management and reinforced by Surabaya Mayor Regulation Number 26 of 2024 on the Implementation of Regional Taxes and Regional Retribution for Public Service Retribution, which regulates electronic parking payment mechanisms through parking meters, e-money, QRIS, mobile banking, bank transfers, or Electronic Data Capture (EDC) machines. This study aims to analyze the implementation of the E-parking policy and its contribution to parking retribution revenue in Surabaya. The research method employed is qualitative descriptive, with data collected through interviews, observations, and documentation at the Surabaya Transportation Agency, particularly the On Street Parking Technical Unit. The results indicate that the E-parking policy has been implemented through the provision of parking meters, the application of cashless payment systems, and monitoring and socialization activities for the public and parking attendants to minimize potential retribution leakage. In general, parking retribution revenue from 2016 to 2025 shows an increasing trend, although fluctuations occurred during certain periods. However, the realized revenue has not yet fully met the targets set by the local government. This condition demonstrates that the implementation of E-parking has contributed to improving parking management and retribution revenue but still requires optimization through strengthened supervision, expansion of E-parking locations, and enhanced socialization to the public and policy implementers.